Step characteristics of international-level skeleton athletes in the starting phase of official races - Oguchi, T.; Ae, M.; Schwameder, H. (Sports Biomechanics, 2021)
The step characteristics of the starting motion of international-level skeleton athletes were investigated in official races as well as the relationship between the start and finish times. The starting motion of 26 male athletes was recorded with four video cameras in Intercontinental and Europe Cups, 2018 and their starting motion was analysed by a three-dimensional direct linear transformation method. The start time showed significant correlation with the finish time as well as the sled speed at the 4 m and 9 m marks. The athletes were divided into two types according to the sled position and the foot for the 1st step: ipsilateral type and contralateral type. The sled speed of the ipsilateral type athletes in the 1st step was higher than that of the contralateral-type athletes. Step length from the 2nd to 5th and 7th steps showed a significant negative correlation with the start time. The international-level skeleton athletes gained a shorter start time due to a large running speed by acquiring the large SL.